Rhesus Macaque Activating Killer Immunoglobulin-Like Receptors Associate With Fc Receptor Gamma (FCER1G) and Not With DAP12 Adaptor Proteins Resulting in Stabilized Expression and Enabling Signal Transduction - Hasan, Mohammad Zahidul; Walter, Lutz (Frontiers in Immunology, 2021)
Activating killer cell immunoglobulin-like receptors (KIR) in macaques are thought to be derived by genetic recombination of the region encoding the transmembrane and intracellular part of KIR2DL4 and a KIR3D gene. As a result, all macaque activating KIR possess a positively charged arginine residue in the transmembrane region. As human KIR2DL4 associates with the FCER1G (also called Fc receptor-gamma, FcR) adaptor, we hypothesized that in contrast to human and great ape the activating KIRs of macaques associate with FcR instead of DAP12. By applying co-immunoprecipitation of transfected as well as primary cells, we demonstrate that rhesus macaque KIR3DS05 indeed associates with FcR and not with DAP12. This association with FcR results in increased and substantially stabilized surface expression of KIR3DS05. In addition, we demonstrate that binding of specific ligands of KIR3DS05, Mamu-A1*001 and A1*011, resulted in signal transduction in the presence of FcR in contrast to DAP12.